Qualidade de vida, condições clínicas e radiográficas de dois implantes não unidos submetidos à carga imediata de overdenture mandibular: estudo piloto - Cavalheiro, Suellen Cristina (2018)
This pilot study evaluated the clinical and radiographic peri-implant conditions of two unsplinted implants immediate loaded with mandibular overdentures, as well, evaluated the oral health related quality of life (OHRQoL) in these patients. Materials and Methods: ten totally edentulous patients received 20 implants with ball attachment, being 6 immediate loaded (test group) and 4 conventional loaded (control group). For OHRQoL assessment, the OHIP-EDENT questionnaire was applied before the implants insertion, 3 and 6 months after. After 6 months of implant insertion, the following clinical parameters were evaluated: probing depth, width of the keratinized mucosa, modified bleeding index, modified plaque index. The marginal bone loss was obtained by analyses of periapical radiographs at the day of implant insertion, 3 and 6 months after. Results:There was a significant improvement of quality of life at 3 months in immediate loaded group and at 6 months at the conventional loaded group comparing to initial time (p<0,05) with no significant difference between groups (p>0,05). There was no significant difference between groups for the clinical and radiographic parameters at 6 months.Conclusion: There was no significant difference between groups in all quality of life, clinical and radiographic parameters, however the immediate load provided a better quality of life before the conventional load. Long term studies may be conducted due to follow peri-implant indices and to obtain success index of theimplants.